An Analysis of New Word Found on Twitter Using the Process of Word-Formation - Rosmilinda Rinche; I Nyoman Udayana; Made Detriasmita Saientisna (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This paper concerns the analysis of New Word Found on Twitter Using the Process of Word-Formation. The aim of this study is to analyze word-formation on words that have just appeared on social media, especially Twitter. The research used in this analysis is a qualitative research method. Source of research data in the study came from the Twitter app found in captions, comment fields, and retweet quotes. When collecting the data, the researchers used several steps, first searched the data in the Twitter app from captions, comment fields, and retweet quotes. Then, collect data containing word formation and classify the data by type. The data is collected and researchers analyze the type and process of word-formation. The results of this study indicate that there are 5 types of word-formation processes found on Twitter. They were derivation, abbreviation, blending, acronyms, and clipping. Of these types, abbreviations were the most common word-formation on Twitter.